Evaluation of lupus anticoagulant, damage, and remission as predictors of pregnancy complications in systemic lupus erythematosus: the French GR2 study. (7th January 2022) - Larosa, Maddalena; Le Guern, Véronique; Guettrot-Imbert, Gaëlle; Morel, Nathalie; Abisror, Noémie; Morati-Hafsaoui, Chafika; Orquevaux, Pauline; Diot, Elisabeth; Doria, Andrea; Sarrot-Reynauld, Françoise; Limal, Nicolas; Queyrel, Viviane; et al.
Abstract: Objectives: The specific roles of remission status, lupus low disease activity state (LLDAS), and damage accrual on the prognosis of pregnancies in women with SLE are unknown. We analysed their impact on maternal flares and adverse pregnancy outcomes (APOs). Methods: We evaluated all women (≥18 years) with SLE enrolled in the prospective GR2 study with an ongoing singleton pregnancy at 12 weeks (one pregnancy/woman). Several sets of criteria were used to define remission, disease activity and damage. APOs included: foetal/neonatal death, placental insufficiency with preterm delivery and small-for-gestational-age birth weight. First trimester maternal and disease features were tested as predictors of maternal flares and APOs. Results: The study included 238 women (98.3% on hydroxychloroquine (HCQ)) with 230 live births. Thirty-five (14.7%) patients had at least one flare during the second/third trimester. At least one APOs occurred in 34 (14.3%) women. Hypocomplementemia in the first trimester was the only factor associated with maternal flares later in pregnancy ( P= 0.02), while several factors were associated with APOs. In the logistic regression models, damage by SLICC-Damage Index [odds ratio (OR) 1.8, 95% CI: 1.1, 2.9 for model 1 and OR 1.7, 95% CI: 1.1, 2.8 for model 2] and lupus anticoagulant (LA, OR 4.2, 95% CI: 1.8, 9.7 for model 1; OR 3.7, 95% CI: 1.6, 8.7 for model 2) were significantly associated with APOs. Conclusion: LA and damage at conception were predictors of APOs, and hypocomplementemia in the first trimester was associated with maternal flares later in pregnancy in this cohort of pregnant patients mostly with well-controlled SLE treated with HCQ. Trial registration: ClinicalTrials.gov, https://clinicaltrials.gov, NCT02450396.